Regulation in the face of uncertainty: the evidence on electronic nicotine delivery systems (e-cigarettes) - Farsalinos KE; Le Houezec J (Dove Medical Press, 2015)
Konstantinos E Farsalinos,1,2 Jacques Le Houezec3,4 1Department of Cardiology, Onassis Cardiac Surgery Center, Kallithea, 2Department of Pharmacy, University of Patras, Patras, Greece; 3Division of Epidemiology and Public Health, UK Centre for Tobacco and Alcohol Studies, University of Nottingham, Nottingham, England, UK; 4Addiction Research Unit, INSERM 1178 (Mental and Public Health), Paris, France Abstract: Tobacco smoking is the largest single preventable cause of many chronic diseases and death. Effective treatments exist; however, few smokers use them and most try to quit by themselves. Most of the tobacco cigarette's toxicity is related to the combustion process. Models of harm reduction applied to tobacco suggest that switching from inhalation of combustible products to a noncombustible nicotine delivery product would likely result in a vast reduction in tobacco-related death and illness. Currently available evidence raises no doubt that electronic cigarettes (e-cigs) are by far less harmful than smoking (although probably not absolutely safe) and have the potential to be the most effective tobacco harm reduction products due to their unique property of resembling smoking and providing satisfaction to the user. A lot of controversy is surrounding e-cigs and their regulation, much of which is based on the precautionary principle. Although monitoring and further research is definitely needed, the arguments used to implement severe restrictions or bans are mostly hypothetical, weakly supported by evidence, and, in some cases, derived from mispresentation or misinterpretation of the study findings. Regulators should keep in mind that the target population is smokers who want to reduce or quit their deadly tobacco consumption. To achieve this goal, smokers should be honestly informed on the relative harmfulness of the different products. E-cigs are not tobacco products and are not used as medications. For this reason, a specific regulatory scheme is needed, separate from tobacco or medicinal products regulation. Regulation should implement specific quality criteria for products, rules for the exclusion of chemicals of reasonable concern, and appropriate testing for possible contaminants. Additionally, manufacturing standards derived from the food industry should be implemented and adjusted for specific conditions related to e-cigs. Finding the appropriate balance between safety and acceptability of use by smokers will be important in achieving the maximum public health benefit. Labeling should be specified, with warnings about exposure to skin or through ingestion and discouragement of use by nonsmokers, related to the presence of nicotine. Finally, advertising and marketing should not be banned, but appropriately regulated in order to encourage use by the intended population while avoiding use by never-smokers. E-cigs should be appealing to smokers (but not to nonsmokers), while availability and pricing should be strong competitive advantages of e-cigs relative to tobacco cigarettes. Keywords: electronic cigarettes, nicotine, smoking, tobacco harm reduction, precautionary principle, regulation